A novel lncRNA lncSAMD11-1: 1 interacts with PIP4K2A to promote endometrial decidualization by stabilizing FoxO1 nuclear localization. (October 2022) - Zhang, Mei; Cai, Xinyu; Liu, Jingyu; Zhou, Jidong; Shi, Qingqing; Jiang, Yue; Kang, Nannan; Zhen, Xin; Wu, Min; Qiu, Panpan; Yan, Guijun; Sun, Haixiang; et al.
Abstract: Decidualization is essential for a successful pregnancy and determines embryo implantation and pregnancy maintenance. Abnormal decidualization is one of the main causes of recurrent implantation failure (RIF). Studies have shown that large amounts of long noncoding RNAs (lncRNAs) are abnormally expressed in endometrial samples from patients with RIF. However, the functional contributions of lncRNAs to decidualization in RIF have not been explored. In this study, we found that lncSAMD11–1:1 was significantly declined in the endometria of patients with RIF. The knockdown of lncSAMD11–1:1 in human endometrial stromal cells (hESCs) restrained decidualization and embryo implantation in vitro, while the overexpression of lncSAMD11–1:1 facilitated hESC decidualization and embryo implantation in vitro and ameliorated decidualization in RIF patients. Mechanistically, lncSAMD11–1:1 and phosphatidylinositol-5-phosphate 4-kinase type 2 alpha (PIP4K2A) translocated out of nucleus and bound to each other during decidualization, thereby inhibiting the phosphorylation of AKT and promoting FoxO1 nuclear localization. These data suggest that lncSAMD11–1:1 might be a critical novel lncRNA functionally required for human decidualization, and the dysregulation of lncSAMD11–1:1 in the endometrium may be a new predisposing factor of RIF.